THE EFFECT OF MURABAHAH, MUDHARABAH, MUSYARAKAH AND CAPITAL ADEQUACY RATIO FINANCING ON PROFITABILITY OF SHARIA COMMERCIAL BANKS IN INDONESIA WITH NON PERFORMING FINANCING RATIO AS MODERATING VARIABLES - Amanda, Jihan (International Journal of Public Budgeting, Accounting and Finance, 2019)
The purpose of this study was to determine the effect of murabahah, mudharabah, musyarakah, and capital adequacy ratios partially and simultaneously on profitability in Islamic Commercial Banks in Indonesia. In addition, this study also aims to test whether non-performing financing variables are able to moderate the relationship between each of the murabahah, mudharabah, musyarakah and capital adequacy ratio variables to profitability in Islamic Commercial Banks in Indonesia. The population of this research is as many as 13 Sharia Commercial Banks with years of observation starting from 2008 to 2017. Samples were selected using the purposive sampling method. The method of data analysis uses multiple regression and moderating regression analysis. The results of this study indicate that murabahah financing and capital adequacy ratios have a positive and significant effect on profitability. Mudharabah financing has a positive and not significant effect on profitability. While Musyarakah financing has a negative and not significant effect on profitability. The results of the moderating variable indicate that non-performing financing has a significant effect as a moderating variable both between murabahah, mudharabah and musyarakah financing towards profitability. Conversely, non-performing financing does not have a significant effect as a moderating variable between capital adequacy ratio to profitability.